Emission constrained economic dispatch for hybrid energy system in the presence of distributed generation and energy storage - Pazheri, Faisal Rehman (AMER Inst Physics, 2015)
Due to the concerns about the increasing price of fossil fuels, greenhouse gas emissions and energy supply sustainability, power utilities are being forced to examine their operational policies. The use of hybrid power system and the minimization of overall generation cost of such systems employing distributed generation and distributed energy storage facilities with limited amounts of pollutants emission is the main objective of the optimization carried out in this work. The analysis considers the generation cost of thermal, renewable and storage based hybrid power plants along with the cost paid for health and environmental damages caused by the emissions. The analysis is carried out using MATLAB simulations with sequential quadratic programming algorithm. It is shown that the actual cost of fossil fuel based electricity generation is higher than that of the renewable power generation if the hidden costs of conventional generation related to environmental impacts are considered as well. (C) 2015 AIP Publishing LLC.